How To Do Science - Lexis, Louise; Julien, Brianna (Open textbook library., 2022)
'How To Do Science' has been written for students of the life sciences who are actively engaged in the scientific process. This guide introduces you to what it means to be a scientist. You will learn about the scientific method and how to carry out many tasks of a scientist, including: designing experiments, visualising data, accessing scientific literature, communicating science, and writing literature reviews.